An Experimental Investigation on Strength Behaviour of Concrete by Partial Replacement of Fine Aggregate with Copper Slag and Cement With Silica Fume - Anwar, Abdullah; Aqeel Ahmad, Syed (International Journal of Computer Sciences and Engineering, 2025)
Concrete is the most widely used building material in civil engineering industry throughout the globe because of its high structural strength and constancy, where the fine aggregate is generally natural sand. The usage of sand in construction activity results in the excessive mining, causing depletion of natural resources resulting increase in scour depth and sometimes flood possibility. Copper Slag waste is most usually made from the copper industry, whereas Silica Fume is a by-product from many manufactures. Chuck out of both copper slag waste and Silica Fume is one of the major environmental problems worldwide today. Hence the reuse of waste material has been emphasized to sustainable growth. This research paper presents a study of the Strength properties of concrete by partial replacement of fine aggregate with copper slag and cement with silica fume. In the present Experimental Investigation, for M40 grade of concrete, fine aggregate (River Sand) was partially replaced with Copper Slag (40%) and cement was partially replaced with Silica Fume from 5% to 15% at an interval of 5%. This research gives a detailed observational study on Compressive strength, split tensile strength, flexural strength at age of 28 days. Test results indicate that the strength properties of concrete were improved having copper slag as a partial replacement of Sand (up to 40%) and Silica fume as a partial replacement of cement (up to 10%).